Annual Survey of Jails: Jurisdiction-Level Data, 1997 ([Verlag nicht ermittelbar], 1998)
This collection provides annual data on jail populations across the nation and examines the "spillover" effect on local jails resulting from the dramatic growth in federal and state prison populations. These data permit an assessment of the demands placed on correctional resources and provide a comprehensive picture of the adult correctional system and changes that occur within the system. Information is available on the number of inmates by sex, race, and adult or juvenile status. Facility characteristics were collected regarding capacity and average daily population.